(untitled) (Fiep Bulletin - online, 2011)
Abstract: The goal of this research was to evaluate the efficiency of a physical therapy treatment program, under the postural reeducation technique combined with the cerebral potentiality, applied to 12 adolescents of both genders, between 11 and 15 years old, who showed alteration in the sensor motor system and struggle in keeping an adequate body posture, evaluated before and after intervention, under the SAPO technique. The intervention in question took 20 sessions, the first phase being the 10 first sessions and the second phase, the 10 final sessions, with medium length of 90 minutes each, 30 minutes for cerebral potentiality, under the binaural heart beats on the alpha frequencies between 8 and 13 HZ and 60 minutes of postural reeducation, using the Philippe Souchard method, on the positions of ‘’true frog in the air’’, ‘’true frog on the ground’’ and ‘’feet in the center’’. The obtained results on the post-intervention of the two phases showed, through resources of descriptive statistic, an improvement in the head alignment, acromions, anterior superior iliac spines, angle of the scapula and the T3 vertebra, with consequent improvement on the body posture.